On the melt pool flow and interface shape of dissimilar alloys via selective laser melting - Yao, Liming (2023)
A simulation model is established to describe the micron-scale flow of dissimilar alloys between IN625 and 316 L. The accuracy of the model has been verified through experiments. It is found that the Marangoni force and the recoil pressure are 6.28 and 58.51 times the surface tension, respectively. Marangoni force, recoil pressure, and surface tension are the key factors influencing the melt-pool convection and shape. When the laser power is increased, the recoil pressure forms a deep keyhole which leads to a rapid increase in the melt-pool depth. The interlayer interface is changed from a weakly staggered shape to a regularly and remarkably staggered and overlapping shape. The specific surface area growth rate (SAR) is increased by as much as 10 times. The Marangoni force, inertial force and surface tension dominate the single-track surface hump formation. When the depth and width of the melt pool are small and the length is large, the inertial force of the melt is significant, and irregular humps are formed on the single-track surface. The formed humps and the SAR substantially increase the bonding strength between the two dissimilar alloys.